2017
DOI: 10.1080/13880209.2017.1300819
|View full text |Cite
|
Sign up to set email alerts
|

Spirodela polyrhiza extract modulates the activation of atopic dermatitis-related ion channels, Orai1 and TRPV3, and inhibits mast cell degranulation

Abstract: Context:Spirodela polyrhiza (L.) Schleid. (Lemnaceae), Spirodelae Herba (SH), has been known to relieve inflammation, urticaria and skin symptoms including pruritus, eczema and rash.Objective: The effects of SH extract on two calcium ion channels, Orai1 and TRPV3, and their potential as novel therapeutics for atopic dermatitis (AD) were investigated. The regulatory role of Orai1 on mast cell degranulation was evaluated.Materials and methods: The dried leaves of SH were extracted by 70% methanol. Effects of SH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…SP extract is used to treat allergic inflammatory diseases, such as atopic dermatitis. Furthermore, SP extract inhibits mast cell degranulation and suppresses IL-4 and IL-13 expression, which is mediated by Th2 cells [21,22,25]. Our study clearly showed that SP EtOH and luteolin suppressed ANO1 activity, which is responsible for nasal hypersecretion in AR, in addition to alleviating electrolyte secretion via ANO1 inhibition in Calu-3 cells (Fig.…”
Section: A B Cmentioning
confidence: 51%
See 1 more Smart Citation
“…SP extract is used to treat allergic inflammatory diseases, such as atopic dermatitis. Furthermore, SP extract inhibits mast cell degranulation and suppresses IL-4 and IL-13 expression, which is mediated by Th2 cells [21,22,25]. Our study clearly showed that SP EtOH and luteolin suppressed ANO1 activity, which is responsible for nasal hypersecretion in AR, in addition to alleviating electrolyte secretion via ANO1 inhibition in Calu-3 cells (Fig.…”
Section: A B Cmentioning
confidence: 51%
“…(SP) is widely used to relieve inflammation, urticaria, and symptoms of skin irritation, including pruritus, eczema, and rash [20,21]. According to a recent report, SP exerts a potential inhibitory effect on the calcium releaseactivated calcium channel, which is encoded by the ORAI1 gene and is responsible for Th2 activation and mast cell degranulation [22][23][24]. In addition, formulations containing SP or its ethanolic extract have been shown to alleviate allergic inflammation and pruritus in mice with atopic dermatitis [21,25].…”
Section: Original Articlementioning
confidence: 99%
“…A 1290 Series high-performance liquid chromatograph (Agilent Technologies, Santa Clara, CA, USA) at The Korea Basic Science Institute, Seoul, Republic of Korea, was used to analyze the FM EtOH constituents as previously described [26]. After injecting 10 l of 5 mg/ml FM EtOH into a 3.0 × 100 mM, 2.7 M Poroshell 120 SB-C18 column (Agilent Technologies), the constituents were separated and identified at a 278 nM wavelength.…”
Section: Fm Etoh Constituent Analysismentioning
confidence: 99%
“…The -hexosaminidase activity was determined by colorimetric assay using p-nitrophenyl N-acetyl-D-glucosamine hydrolysis, as previously described [26,27]. RBL-2H3 mast cells were seeded in 48-well plates (2.5 × 10 5 cells/ml) and incubated for 24 h before sensitization with 1.0 mg/ml anti-dinitrophenyl (DNP)-IgE for 3 h followed by discarding the solution and washing the cells four times with PBS.…”
Section: -Hexosaminidase Activity Assaymentioning
confidence: 99%
“…To determine the effect of BC and PC on ORAI1 and TRPV3 activity, whole-cell patch clamping was used (Nam et al, 2016(Nam et al, , 2017. All experiments were performed at room temperature.…”
Section: Electrophysiologymentioning
confidence: 99%